(untitled) (Journal of Parents and Teachers, 2014)
Brión is an eminently rural municipality of the region of Santiago de Compostela. In 1996, the REDEVOL project was launched together with seven other municipalities with similar characteristics. This project aims to promote different forms of collaboration between different community agents and promote a culture based on solidarity.